MECHANISMS OF SHAPING LINGUISTIC THINKING THROUGH PSYCHOLINGUISTIC TECHNOLOGIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores the theoretical and methodological foundations as well as the practical mechanisms of shaping linguistic thinking through psycholinguistic technologies. It examines the relationship between language and thought within the psycholinguistic framework, the development of students ’communicative competence, the modeling of linguo-psychological processes, and the effectiveness of applying innovative technologies in education. The study also highlights the interconnectedness of perception, memory, speech, and cognition in the formation of linguistic consciousness.